2010
DOI: 10.3109/00207450903585290
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Differentiation of Human Embryonic Stem Cells into Oligodendrocyte Progenitors for Application in a Rat Contusion Model of Spinal Cord Injury

Abstract: This study utilized a contusion model of spinal cord injury (SCI) in rats using the standardized NYU-MASCIS impactor, after which oligodendrocyte progenitor cells (OPCs) derived from human embryonic stem cell (ESC) were transplanted into the spinal cord to study their survival and migration route toward the areas of injury. One critical aspect of successful cell-based SCI therapy is the time of injection following injury. OPCs were injected at two clinically relevant times when most damage occurs to the surrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 42 publications
2
76
0
Order By: Relevance
“…Different protocols have been developed later using different induction factors, including sonic hedgehog (Shh) protein, PDGF, insulin-like growth factor (IGF)-1, bone morphogenetic protein antagonists such as noggin, neurotrophic factors such as neurotrophin (NT)-3 and ciliary neurotrophic factor, with or without EGF [24][25][26][27][28] . High-purity OPCs were obtained, and they also showed remyelination capacity in animal study [29] . The main drawback of these PDGF-dependent protocols is their lengthy (10-14 wk) and complicated procedures with multiple growth factors and multiple steps of suspension and adherent cultures, which are difficult and expensive to scale up for generating cells needed for clinical studies.…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different protocols have been developed later using different induction factors, including sonic hedgehog (Shh) protein, PDGF, insulin-like growth factor (IGF)-1, bone morphogenetic protein antagonists such as noggin, neurotrophic factors such as neurotrophin (NT)-3 and ciliary neurotrophic factor, with or without EGF [24][25][26][27][28] . High-purity OPCs were obtained, and they also showed remyelination capacity in animal study [29] . The main drawback of these PDGF-dependent protocols is their lengthy (10-14 wk) and complicated procedures with multiple growth factors and multiple steps of suspension and adherent cultures, which are difficult and expensive to scale up for generating cells needed for clinical studies.…”
Section: Cellsmentioning
confidence: 99%
“…Kerr et al [29] , 2010 All the steps of hPSC expansion and differentiation were performed on VN-PAS. a P < 0.05 vs MMM.…”
Section: Differentiation From Pscsmentioning
confidence: 99%
“…The use of noggin has been shown to broadly act by inhibiting bone morphogenetic proteins (BMPs) to suppress mesendodermal lineage patterning, promoting neural differentiation of hPSCs [23,26,43,59], Izrael et al, have shown that noggin also plays a role in the lineage specification of OPCs, potentiating the maturation toward oligodendrocytes [21]. Further, adding noggin at these early stages of hPSC development decreased noggin-mediated maturation, supporting the differentiation toward a glial lineage [21].…”
Section: Alsanie Niclis and Petratosmentioning
confidence: 99%
“…Nistor et al, Kang et al, and Kerr et al, have all used matrigel as an ECM during the differentiation into NPs, while the Sundberg et al, and Hu et al, groups have either used a combination of laminin, collagen IV, and nidogen-1, or a combination of laminin and poly-l-lysine, respectively [20,22,[25][26][27][28]. However, the use of ECMs is not essential during hPSC to NP culture stages as Gil et al, and Izrael et al, have not incorporated ECMs within their protocols [21,23].…”
Section: Extraneous Signals For the Differentiation To Nps And Their mentioning
confidence: 99%
“…Our SCI model has been previously described (Agrawal et al, 2008(Agrawal et al, , 2010a(Agrawal et al, , 2010bAl-Nashash et al, 2009;All et al, 2009All et al, , 2010All et al, , 2012Iyer et al, 2010;Kerr et al, 2010;Bazley et al, 2011Bazley et al, , 2012aBazley et al, , 2012b. A laminectomy was performed by removing the T8 thoracic vertebra to expose the dorsal surface of the spinal cord without opening the dura mater.…”
Section: Laminectomy and Contusion Injurymentioning
confidence: 99%